Etyczny wzór lobbingu: analiza kodeksów regulujących działalność lobbingową - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2012)
Self-regulation initiatives are undertaken by many lobbing circles in various countries. The key element of those initiatives are codes of ethics including a postulated model of lobbying activities, a specific pattern of ethical standards of lobbying. The aim of the article is a reconstruction of this pattern on the basis of the analysis of eight codes representing American, Polish, British, European and German lobbying. The analysis leads to the following conclusions. An axiological base of the lobbyist profession is created by such values as honesty, reliability, integrity, trust, professionalism, civil responsibility, openness, transparency, loyalty, respect, courtesy. Norms included in the codes are concentrated on the following issues: legality, transparency of actions, care of reputation and dignity of profession, avoiding corruption, conflict o f interest, customer relationship, duties toward society, public relations. A weak element of lobbying self-regulation is a system of norm execution.